2013
DOI: 10.2147/dddt.s39247
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in patients with AFB smear-positive sputum who receive inappropriate antituberculous treatment

Abstract: BackgroundAcid-fast bacilli (AFB) smear-positive sputum is usually an initial clue in the diagnosis of pulmonary tuberculosis (TB); however, the test is not disease-specific. Nontuberculous mycobacterium-related colonization or lung disease often has AFB smear-positive sputum results, and physicians may prescribe unnecessary antituberculous drugs for these patients. The aim of this study was to analyze the clinical characteristics of patients with AFB smear-positive sputum who received unnecessary anti-TB trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…However, the administration of unnecessary empiric anti-TB treatment is not uncommon in real world practice and patients might suffer from the adverse effects of anti-TB drugs. Our colleagues (Shih-Chieh Chang, et al) issued an article that revealed 40.4% of patients with positive sputum AFB stains did not have pulmonary TB in Taiwan [ 20 ]. According to Chang’s results, among patients who had positive sputum AFB stains without pulmonary TB, 25.8% were prescribed anti-TB treatment and 44% of them developed various adverse effects (hepatitis: 32%; skin rash: 20%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of unnecessary empiric anti-TB treatment is not uncommon in real world practice and patients might suffer from the adverse effects of anti-TB drugs. Our colleagues (Shih-Chieh Chang, et al) issued an article that revealed 40.4% of patients with positive sputum AFB stains did not have pulmonary TB in Taiwan [ 20 ]. According to Chang’s results, among patients who had positive sputum AFB stains without pulmonary TB, 25.8% were prescribed anti-TB treatment and 44% of them developed various adverse effects (hepatitis: 32%; skin rash: 20%).…”
Section: Discussionmentioning
confidence: 99%
“…Only about 20 -40% of pulmonary TB patients are smear-positive, while rest of the patients had either smear-negative or sputum-scarce disease. [5,6] The key to this challenge is having a more accurate and rapid diagnostic modality and obtaining a high-quality biological specimen. Bronchoscopy with Bronchoalveolar Lavage (BAL) is routinely performed for these set of patients in a suspected case of pulmonary tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with positive AFB smear results may be directly diagnosed as PTB and received a long-term antituberculosis treatment, in the absence of specimen culture and strain identi cation. According to Chang's study, of the patients with AFB smear-positive sputum but no PTB, 18.5% were later diagnosed with NTM-LD, and 32% were a icted with NTM colonization [20]. Once NTM-LD is misdiagnosed as PTB and given chemotherapy, there will be not only a high risk of adverse reactions, but also a long course of treatment, poor e cacy, and a heavy economic burden [7,8].…”
Section: Discussionmentioning
confidence: 99%